Analysis of the Factors Influencing the Coding Quality in East Java Hospital of Indonesia: Diabetes Mellitus as A Case Study - Markam, Hosizah; Ningsih, Kori Puspita; Widjaja, Lily; Nisak, Umi Khoirun; Marzo, Roy Rillera; Siswati (Window of Health : Jurnal Kesehatan, 2025)
Code precision has received significant attention due to the increased utilization of encoded procedural data. Coding errors have been documented in multiple research investigations. This study aims to assess the variables that affect coding quality. The prevalence of diabetes has increased substantially in the past two decades and is a significant cause of morbidity and mortality. Method: This study was conducted in 2 hospitals in East Java, Indonesia, that were selected through simple random sampling from a population of hospitals meeting the predefined inclusion criteria. The bed capacities of these hospitals are 211, with details of 62 and 149, respectively, for the specialised ones. The sample in this study was 60 medical record files taken randomly in 2022 in the case of diabetes mellitus. The result showed coding quality testing uses six elements: reliability, accuracy, relevancy, timeliness, completeness, and legibility. Data analysis was carried out analytically using the Fisher Exact test. The results of the study from 60 samples showed that four elements were significant out of a total of 6 aspects of coding quality elements. The four essential elements consisted of Accuracy (p=0.001), Reliability (p=0.001), Completeness (p=0.046), and Legibility (p=0.046). Reliability elements also impact coding accuracy or vice versa (p=0.001); Completeness also affects Legibility and vice versa (p=0.046). The odds ratio value of each component shows that Reliability and Accuracy are 8.782, which means that Reliability can increase Accuracy 8 times and vice versa. Meanwhile, completeness and legibility are at 3.818, which means completeness also increases legibility by three times and vice versa. The Hospitals should consider four significant coding quality elements, including completeness, accuracy, reliability, and legibility, for use in coding audits. Timeliness and Relevance were insignificant.